Space mission as a service (SMaaS): General-purpose computing on space - Leonardo Camargo-Forero; Julián G. Rodríguez-Ferreira; Carlos J. Barrios-Hernández (Revista Colombiana de Computación)
Given the critical nature of their missions, space systems such as satellites, probes, spacecraft, etc., are commonly embedded with specific hardware and software solutions. While this approach has led to numerous achievements, it has also limited the available capacities of a spacecraft and the potential integration between multiple units. In this work, we propose the concept of Space Mission as a Service (SMaaS), a set of strategies for deploying space systems capable of general-purpose computing, embedded Artificial Intelligence, user transparency, and flexibility towards the integration between multiple spacecraft. Such strategies will include evaluating standard operating systems and embedded companion computers, such as the NVIDIA® Jetson Series, under space conditions, common AI frameworks, High-Performance Embedded Computing, and cloud computing as an integrator between space computing devices and earth ground stations. As a demonstration, we intend to evaluate such strategies within the scope of a project consisting of devising the computing on-board system of a nanosatellite belonging to the Colombian Air Force. The possibilities are endless if a spacecraft were embedded with a companion computer with the necessary hardware and software components to execute general-purpose computing and artificial intelligence software. On-board data preprocessing, optimized space-earth download bandwidth, vision-based navigation, autonomous collision avoidance, and overall higher levels of autonomy are a few examples of the potential of this approach that could lead to the implementation of a supercomputer in space.